ENGLISH TEACHING LEARNING PROCESS IN BILINGUAL CLASSROOM :A Descriptive Study at a Bilingual Boarding School in Bandung - Perina Widiani, - (2011)
This paper is entitled "English Teaching Learning Process in Bilingual Classroom: A Descriptive Study at Bilingual Boarding School". The purposes of this study are to find out the techniques applied and the materials employed in English teaching learning process in bilingual boarding school.The qualitative approach and descriptive method were used in gaining the data of this study. In collecting data, the researcher used two kinds of techniques. Those were observation and interview. Since this study used a descriptive method as mentioned previously, the obtained data were analyzed qualitatively. It means that the data were recorded, transcribed and concluded respectively.The result showed that there were various techniques developed and some materials were employed over the course of time. Based on the observation, the teachers used controlled, semi controlled and free techniques in teaching learning process. In controlled techniques, the teachers applied warm up, setting, content expanation, testing, and checking. For semi controlled techniques, preparation, question-answer referential, and information transfer were also applied by the teachers in the classrooms. Meanwhile, for free techniques, the teachers applied games, interview, and discussion.There were three material components in the textbook; language focus materials, vocabulary materials, and skill materials. In terms of the materials used in the classroom, the teachers also used games and cassette.